LUNG BULLAE DUE TO SEPTIC PULMONARY EMBOLISM IN A 4-YEAR-OLD CHILD: A CASE REPORT - Widiastari, Erina Febriani; Graha, Wirya Ayu; Pardede, Marolop (Transpublika Publisher, 2022)
Bullous lung disease in pediatric patients is a rare case. The etiology of lung bullae is cigarette smoking history, pulmonary sarcoidosis, alpha 1-antitrypsin deficiency and many more. One of the treatments for lung bulla is surgical approach. We present a case of 4-year-old girl with lung bulla due to septic pulmonary embolism. Primarily the patient was admitted with a decrease in consciousness, fever, cough and dyspnea. A CT scan revealed bilateral bullae, multiple nodules in various size, mostly with internal cavities and feeding vessel sign suggestive of a septic pulmonary embolism accompanied by a pneumothorax. We did thoracotomy, wedge resection and pleurodesis, the outcome was clinical improvement and no postoperative complication occurred. Thoracotomy, wedge resection and pleurodesis can be considered as a treatment for lung bulla in pediatric population, so this case report may provide guidance on management of these cases for clinicians.